Factors associated with the length of hospital stay of women undergoing cesarean section - Pereira,Samire Lopes (2019)
ABSTRACT OBJECTIVE To evaluate whether age group, complications or comorbidities are associated with the length of hospitalization of women undergoing cesarean section. METHODS A cross-sectional study was carried out between June 2012 and July 2017, with 64,437 women undergoing cesarean section and who did not acquire conditions during their hospital stay. Hospital discharge data were collected from national health institutions, using the Diagnosis-Related Groups system (DRG Brasil®). The DRG referring to cesarean section with additional complications or comorbidities (DRG 765) and cesarean section without complications or associated comorbidities (DRG 766) were included in the initial diagnosis. The influence of age group and comorbidities or complications present at admission on the length of hospital stay was assessed based on the means of the analysis of variance. The size of the effect was verified by Cohen’s D, which allows evaluating clinical relevance. The criticality levels were identified using the Duncan test. RESULTS The longest length of hospital stay was observed in the age group from 15 to 17 years old and among those aged 45 years old or more. The hospital stay of women with complications or comorbidities at the time of admission was also longer. Moreover, it was noted that the increase in criticality level was associated with an increase in the mean length of hospital stay. CONCLUSIONS The length of hospital stay of women is higher among those belonging to the age group ranging from 15 to 17 years old and for those aged 45 years old or more. The presence of associated comorbidities, such as eclampsia, pre-existing hypertensive disorder with superimposed proteinuria and gestational hypertension (induced by pregnancy) with significant proteinuria increase the length of hospital stay. This study enabled the construction of distinct criticality level profiles based on the combination of age groups and the main comorbidities, which were directly related to the length of hospital stay.